Investigation of the influence of crushed sand on carbonation of Mortar: Physical and microstructural analysis - Emmanuel A.M. Elat; Alexandre Pierre; Prosper Pliya; Myriam Duc; Michel Mbessa; Albert Noumowé (Cleaner Materials)
The use of crushed sand instead as a substitute for river sand has gained importance in construction practices due to the limited availability of river sand. This study examines the physical and microstructural impacts of crushed sand on mortar carbonation. Using X-ray Diffraction (XRD), Thermo-Gravimetric Analysis (TGA), and Scanning Electron Microscopy (SEM). We highlight the influence of substituting river sand with crushed sand after exposure to 3 % CO2 in an accelerated carbonation chamber for 28 days. The mass fractions of Ca(OH)2 and CaCO3 were determined by thermogravimetric analysis, and a decrease in porosity was observed with an increasing proportion of crushed sand in the mixture. Partial or total substitution of river sand with crushed sand, for environmental purposes, shows improved resistance against CO2 attack. Our study reveals the beneficial effects of crushed sand in reducing porosity and carbonation compared to river sand.